3x+11x-20=0

Simple and best practice solution for 3x+11x-20=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+11x-20=0 equation:


Simplifying
3x + 11x + -20 = 0

Reorder the terms:
-20 + 3x + 11x = 0

Combine like terms: 3x + 11x = 14x
-20 + 14x = 0

Solving
-20 + 14x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 14x = 0 + 20

Combine like terms: -20 + 20 = 0
0 + 14x = 0 + 20
14x = 0 + 20

Combine like terms: 0 + 20 = 20
14x = 20

Divide each side by '14'.
x = 1.428571429

Simplifying
x = 1.428571429

See similar equations:

| 2x+10=5x+25 | | 84=3w | | 17-(3+b)=b | | 8a+15+a^2=0 | | 12x+16=4x+56 | | 5000x^2+60x=0 | | x+3-4x=6x+10 | | X-5=7-x | | 500x^2+6x=0 | | 1+(-3)= | | 3y-2(y-1)=6-(4+1) | | 0=k^2+12k+32 | | -7+4x=6x-5x | | 3x+18=99 | | 11x-y=-15 | | -66=2b-6(6+2b) | | 3x^2-6x-12y+3y^2-12=0 | | 6x+16=-5 | | 2u=38 | | -6x-1+3x=-7x-7 | | 8(y+6)+27=99 | | 16a-8a-8b= | | y=x+(x*1.2) | | 3x^2-6x-12y+3y^2+12=0 | | 0.33x+2=0.33x+1 | | 2(x-3)-5x=6 | | 1.6x-4.9=6.3 | | -46-36= | | x+5x-5=3x+8 | | 4p+6p+9q= | | -16x^2+48x+640=0 | | 7p-5=h+6+8 |

Equations solver categories